1994
DOI: 10.1111/j.1432-2277.1994.tb01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Early infiltration of renal allografts with 27E10-positive macrophages and graft outcome

Abstract: Recently, we have demonstrated that acute cellular rejection is correlated with a massive infiltration of 27E10-positive macrophages. To examine the distribution of macrophage differentiation markers in the infiltrate in the very early post-transplantation period, two biopsies were taken intraoperatively, approximately 1 h following reperfusion, in each of 16 renal transplant recipients. One biopsy was taken for conventional histology and the other biopsy was snap-frozen. The sections were stained using an ABC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The finding of very early activation of MRP8/14-positive macrophages in this study is consistent with our previous observations with 1-h renal transplant biopsies, which indicated very early involvement of activated MRP8/14-positive macrophages and granulocytes in the immune response to the allograft (35). MRP8/14-positive macrophages and neutrophils are also the first cells to arrive at the inflammatory site in many animal models (12).…”
Section: Discussionsupporting
confidence: 92%
“…The finding of very early activation of MRP8/14-positive macrophages in this study is consistent with our previous observations with 1-h renal transplant biopsies, which indicated very early involvement of activated MRP8/14-positive macrophages and granulocytes in the immune response to the allograft (35). MRP8/14-positive macrophages and neutrophils are also the first cells to arrive at the inflammatory site in many animal models (12).…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies have shown an association between extent of CI MO infiltration and poor graft survival [16,[19][20][21]37]. Differences in patient population, immunosuppression, and treatment of acute rejection may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have demonstrated that glomerular and interstitial monocyte/macrophage (MO) infiltration in acute rejection have a detrimental effect on graft survival [16][17][18][19][20][21][22][23][24][25][26], and are associated with diffuse PTC C4d deposition in acute rejection [27]. In view of the correlation of PTC C4d deposition with reduced graft survival [6,[9][10][11][12], it is uncertain whether MO infiltration is a significant independent predictor of poor allograft outcome.…”
mentioning
confidence: 99%
“…Macrophage accumulation can be found early after transplantation [55] and its persistence in the allograft portends a poor prognosis [56]. Girlanda et al demonstrated that both monocytes and T cell infiltrates are present in rejecting allografts, but allograft dysfunction was only quantitatively associated with monocyte infiltration [57].…”
Section: Macrophages In Acute Allograft Rejectionmentioning
confidence: 98%